Aplikasi Building Information Modeling (BIM) Menggunakan Software Tekla Structures Pada Konstruksi Gedung Rumah Sakit Melati Husada Sukun, Kota Malang - Ignatius Dagur; Nawir Rasidi; Handika Setya Wijaya; Dipa Supriyanti (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
The development of Building Information Modeling (BIM) technology has made an important contribution to improving efficiency, accuracy, and data integration in the planning and implementation of construction projects. The application of BIM enables comprehensive visualization of buildings, control of implementation time, and preparation of more measurable cost estimates. This study discusses the application of BIM in the construction project of Melati Husada Hospital in Malang City using Tekla Structures software as the main structural modeling tool. The objectives of this study are to produce a three-dimensional (3D) structural model, integrate the work schedule into four dimensions (4D), and compile a five-dimensional (5D) construction cost estimate. The method used is a case study method using project shop drawing data as the basis for modeling. Modeling is carried out on the main structural elements, including foundations, beams, columns, slabs, and floor plates, in accordance with the building's structural design. The resulting 3D model is then combined with the project implementation schedule to form a 4D construction simulation so that the sequence of work can be visualized in a more planned and systematic manner. In addition, 5D modeling is used to generate construction cost estimates based on the volume of work obtained from the BIM model. The results of the study show that all main structural elements were successfully modeled in 3D. The 4D simulation shows that the project will commence on July 8, 2025, and be completed on December 23, 2025. The estimated cost of structural work includes foundation, sloof, column, beam, and floor slab work, with a total construction cost of IDR 3,215,280,913.